2005
DOI: 10.1109/tdmr.2005.843831
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of LC oscillator reliability

Abstract: In this paper, MOS device degradations due to hot carrier and gate oxide breakdown are shown experimentally, and their effects on the NMOS LC oscillator have been evaluated analytically and through SpectreRF simulation. The reduction in transconductance of the differential pair transistors may cause the oscillation to cease. The amplitude of oscillation reduces as the equivalent tank resistance decreases due to the breakdown effect on the MOS varactor. The reduction of amplitude reduces the tank capacitances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Various studies have shown that the first failures affecting a component appear sooner for nanometric technologies than for older technologies [14]. Even if functionality is often preserved especially in digital circuits [15], many circuit characteristics such as operating frequencies, current consumption, leakage current [15], noise [16], gate capacitance, or gate oxide resistance [17] can be noticeably modified. Fig.…”
Section: Effect Of Intrinsic Failures On Cmos Device Characteristicsmentioning
confidence: 99%
“…Various studies have shown that the first failures affecting a component appear sooner for nanometric technologies than for older technologies [14]. Even if functionality is often preserved especially in digital circuits [15], many circuit characteristics such as operating frequencies, current consumption, leakage current [15], noise [16], gate capacitance, or gate oxide resistance [17] can be noticeably modified. Fig.…”
Section: Effect Of Intrinsic Failures On Cmos Device Characteristicsmentioning
confidence: 99%
“…In an LC circuit, the frequency fi c at which the circuit resonates is given by the following equation (Mansour et al (2004), Sadat et al (2005)):…”
Section: Lc Oscillatormentioning
confidence: 99%
“…Diese Topologie wurde vor allem bevorzugt, weil ein solcher VCO hohe Frequenzen bis 13 GHz erzeugen kann. Die Designkonzepte von (Hajimiri and Lee, 1999;Sadat et al, 2005;Razavi, 2001;Shu and Sanchez-Sinencio, 2005) L min =240 nm und einer Breite von W =10 µm ermittelt. Die Abschätzung erfolgte nach der Formel (Lee, 2004):…”
Section: Ghz Cmos-vco-designunclassified